2000
DOI: 10.1128/iai.68.5.2424-2430.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 and Interleukin-10 Are Involved in Host Resistance toStaphylococcus aureusInfection through Regulation of Gamma Interferon

Abstract: Our previous study showed that gamma interferon (IFN-␥), a T-helper 1 (Th1)-type cytokine, plays a detrimental role in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 38 publications
6
69
1
1
Order By: Relevance
“…Although a significant difference was observed transiently in mean clinical scores between rIL-4 vs vehicle-treated mice, the final outcome (mean clinical score of þ 4, or perforation), confirmed by slit lamp and histopathology, was not changed by injection of the cytokine. In contrast, in other studies, 29 using a mouse model of S. aureus intravenous challenge, which, in common with our susceptible B6 mouse ocular model, is associated with increased disease that is dependent upon a Th1-type response and IFN-g production, it was found that IL-4 and IL-10 were protective, probably owing to regulation of IFN-g. We have as yet not tested the anti-inflammatory effects of IL-10 or IL-4 and IL-10 in combination. We would predict that either IL-10 alone, or with IL-4, may attenuate disease in our susceptible mouse model.…”
Section: Discussioncontrasting
confidence: 43%
“…Although a significant difference was observed transiently in mean clinical scores between rIL-4 vs vehicle-treated mice, the final outcome (mean clinical score of þ 4, or perforation), confirmed by slit lamp and histopathology, was not changed by injection of the cytokine. In contrast, in other studies, 29 using a mouse model of S. aureus intravenous challenge, which, in common with our susceptible B6 mouse ocular model, is associated with increased disease that is dependent upon a Th1-type response and IFN-g production, it was found that IL-4 and IL-10 were protective, probably owing to regulation of IFN-g. We have as yet not tested the anti-inflammatory effects of IL-10 or IL-4 and IL-10 in combination. We would predict that either IL-10 alone, or with IL-4, may attenuate disease in our susceptible mouse model.…”
Section: Discussioncontrasting
confidence: 43%
“…Potential sources of this early IL-4 release include mast cells (61) and NK-T cells (4). IL-4 is also released in response to a number of other extracellular and intracellular bacteria (19,56,68). Like IL-10, IL-4 may be anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs), macrophages, NK cells, NK-T and TCR-␥/␦-T cells, mast cells, neutrophils, endothelial cells, and fibroblasts can collectively release these mediators and subsequently become activated in response to them. Anti-inflammatory cytokines, such as IL-4 and IL-10, can also be released in response to bacterial challenge (68). Following the innate response to extracellular bacteria, long-lived, adaptive immunity develops, and this is primarily mediated by antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recentemente a importância das células T e das citocinas do sistema imune inato nas infecções por S. aureus têm sido objeto de estudo [15,16]. Foi observado que as células T desempenham um papel fundamental na prevenção da infecção por S. aureus, como demostrado em modelos de infecções local e disseminada.…”
Section: Introductionunclassified